2007
DOI: 10.1080/00754170701195728
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research: a psychotherapeutic assessment model for siblings in care

Abstract: This paper focuses on the aspects of a qualitative research project that examines an assessment protocol for the placement of siblings in foster care and/or future adoption. A brief description of the background to the study and the research design is given. Evaluating the material from the quantitative instruments used and the psychotherapeutic assessments, the author identified two predominant themes. The first, cumulative trauma, pointed to the pervasive nature of the children's early experiences, as manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
9
1
1
Order By: Relevance
“…Contrary to some authors' conclusions that social workers underestimate the meaning of sibling relationships (e.g. Hindle, 2007), this current study supports Atwool's (2013) findings that their importance is recognised, and perhaps sometimes over-rated.…”
Section: Sibling Relationships As Non-abusive and Of Intrinsic Valuecontrasting
confidence: 98%
“…Contrary to some authors' conclusions that social workers underestimate the meaning of sibling relationships (e.g. Hindle, 2007), this current study supports Atwool's (2013) findings that their importance is recognised, and perhaps sometimes over-rated.…”
Section: Sibling Relationships As Non-abusive and Of Intrinsic Valuecontrasting
confidence: 98%
“…Some studies have emphasised the trauma experienced by siblings who become looked‐after and enter foster care and/or adoption. Adopting a psychotherapeutic perspective, Hindle () describes children's experiences of fear and loss in relation to sibling relationships and concluded that adults can underestimate the meaning attached to sibling relationships by children when making placement decisions. Cossar and Neil () also stress the need to address children's feelings of loss when separated from siblings.…”
Section: Resultsmentioning
confidence: 99%
“…Some concerns regarding the ability of professional practices to adequately address issues related to sibling relationships and placement decisions were evident (Hindle, ; James and others, ). Hollows and Nelson's () study of professional judgement making in relation to the placement of large sibling groups (four children or more), concluded that there needs to be a move away from the application of universal answers applied to sibling placement decisions in the name of equality and based on an ideal of the ‘least detrimental alternative’.…”
Section: Resultsmentioning
confidence: 99%
“…While splitting up siblings was a question in the majority of cases, their antecedent and current circumstances varied considerably. In only one case did the outcome of this procedure point to separating children who were living together (Martin and Callum, above) and in general we have tended to find more positives in sibling relationships than the foster carers who had or were looking after the children did, a finding similar to that reported by Hindle (2007). This mismatch in perception raises the crucial issue of the extent to which the time in the video suite represents what really goes on at home.…”
Section: Limitationsmentioning
confidence: 51%